Characterization of the spatial distribution of the whitefly-transmitted virus complex in yellow squash fields in Southern Georgia, USA - Codod, Clarence B.; Severns, Paul M.; Sparks, Alton N.; Srinivasan, Rajagopalbabu; Kemerait, Robert C.; Dutta, Bhabesh (Frontiers in Agronomy, 2022)
A two-year study was conducted in 2019 and 2020 to characterize the spatial distribution of whitefly-transmitted virus complex (WTVC) in experimental and commercial yellow squash (Cucurbita pepo) fields in southern Georgia, USA. Field trials planted in Tifton, Georgia, USA were comprised of 30 rows of squash (variety: Gentry) divided into 300 quadrats. Six commercial fields in Tift, Worth, and Colquitt Counties in Georgia, USA were surveyed. In each field, 10 rows of plants per field were partitioned into 70 quadrats so that their approximate location could be mapped and disease incidence tracked in space over time. Plants in each quadrat were visually assessed for TVC symptoms at seven-day intervals (experimental fields) or at fourteen-day intervals (commercial fields). The spatial distribution of WTVC in a one-dimensional space was determined through ordinary runs analysis and in two-dimensional space through spatial autocorrelation analysis and spatial analysis by distance indices (SADIE). Ordinary runs analysis down and between rows suggested that disease was more likely to be transmitted from infected plants within rows than across rows. WTVC incidence in space was positively correlated with adult whiteflies on squash leaves taken one or two weeks prior to the assessment of virus incidence coinciding with latent period of Geminiviruses. SADIE generated disease severity maps indicated a shift from sparse and randomly distributed disease early in the infection cycle to denser, more aggregated patterns later in time in both experimental and commercial fields. Contour plots of interpolated indices from SADIE analysis suggested an edge effect on the spatial distribution of WTVC in experimental fields as well as in two of the commercial fields. An understanding of the shift from random to aggregated distribution and the edge effect on WTVC incidence are considerations for refining current management strategies.